1982
DOI: 10.1097/00000658-198210000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Function in Patients with Angina-Type Chest Pain and Normal Coronary Angiograms

Abstract: Ten per cent of patients with angina pectoris have normal coronary arteries and cardiac function and, despite this reassurance, continue to have chest pain. Since pain of cardiac or esophageal origin is clinically difficult to differentiate, 50 patients with severe chest pain, normal cardiac function, and normal coronary arteriography with ergotamine provocation were evaluated with a symptomatic questionnaire and esophageal function test. On 24-hour esophageal pH monitoring, 23 patients had abnormal reflux, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
77
1
11

Year Published

1986
1986
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(93 citation statements)
references
References 16 publications
4
77
1
11
Order By: Relevance
“…Previous studies that investigated patients with non-cardiac chest pain in secondary care using oesophageal endoscopy and pH monitoring have reported the oesophagus to be a potential origin of non-cardiac chest pain in up to two-thirds of patients, with GORD being the most likely cause. [18][19][20][21] A study in UK primary care reported that IHD was ruled out in half of all patients consulting with chest pain, and that the chest pain had an oesophageal origin in 10% of patients. 22 Similarly, in this study it was found that 10% of patients with non-specific chest pain reported gastrointestinal complaints such as GORD, dyspepsia, or peptic disease during the year preceding the index date, and that 3% of patients with non-specific chest pain had previously received a GORD diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Previous studies that investigated patients with non-cardiac chest pain in secondary care using oesophageal endoscopy and pH monitoring have reported the oesophagus to be a potential origin of non-cardiac chest pain in up to two-thirds of patients, with GORD being the most likely cause. [18][19][20][21] A study in UK primary care reported that IHD was ruled out in half of all patients consulting with chest pain, and that the chest pain had an oesophageal origin in 10% of patients. 22 Similarly, in this study it was found that 10% of patients with non-specific chest pain reported gastrointestinal complaints such as GORD, dyspepsia, or peptic disease during the year preceding the index date, and that 3% of patients with non-specific chest pain had previously received a GORD diagnosis.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Gastrooesophageal reflux is the most common oesophageal abnormality in this context, 1 and acid suppression has been shown to ameliorate the symptoms. 2 Various motility abnormalities can be demonstrated in up to one-third of patients.…”
Section: Introductionmentioning
confidence: 99%
“…A DRGE é a principal anormalidade identificada em pacientes com DTOI, com prevalência entre 21,6% e 63,5% (17,22,28,32,37,40) , em estudos empregando a pHMP . Neste estudo, a pHMP foi anormal em 35% dos casos e destes, apenas dois pacientes apresentavam esofagite erosiva à EDA, achados semelhantes à experiência nacional, que descreve DRGE em pacientes com DTOI em 39% (40) e 51,4% (44) dos casos.…”
Section: Discussionunclassified